Local communities’ intention to create cultural tourism destinations in southern Tanzania tourist circuit: extending the full version of theory of planned behaviour - Emmanuel, Samwel Mtani (2023)
The partaking of rural communities in cultural tourism activities is not appealing in the southern Tanzanian tourist circuit. Literature has indicated that some communities had developed unfavourable attitudes towards heritage tourism, had a low communal spirit, and lacked knowledge, skills, and external support. Accordingly, an expanded version of the theory of planned behaviour (TPB) was used to collect two phases of qualitative and quantitative data to confirm the study's research hypotheses and provide insightful information to policymakers. This was done with the addition of four-dimensional community awareness constructs. Thirty key informants were chosen on purpose from two villages (Kalenga and Matamba) whose residents occasionally engage in cultural tourist activities for the qualitative data. The data were organized into themes and categories using an inductive content analysis. The descriptive findings revealed that ten control beliefs, nine behavioural beliefs, four normative injunctive views, three normative descriptive beliefs, and four normative descriptive beliefs v significantly influence or discourage local populations' decisions to engage in cultural tourist activities. A household survey was carried out with 392 respondents chosen randomly from eight villages in the Iringa, Mbeya, Njombe, and Ruvuma regions to gather quantitative information for generalizing the association between variables. The reliability and validity of the data were validated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), respectively. The covariance-based structural equation model (CB-SEM) was used to test the validity of the hypotheses. The results suggest that the significant positive relationships toward the behavioural intention to create cultural tourism destination among the local communities of the southern Tanzania tourist circuit in the near future could be generated by local communities’ attitudes, subjective injunctive norms, perceived behavioural control, and the added dimensional constructs of community awareness which are cultural resources identification, and cultural resources management. The new findings on mediation effects indicate that as the local communities’ awareness of cultural resources identification and cultural resources management increase, their motivation to comply with specific referrers’ motivation also increases their behavioural intention to create cultural tourism destinations. Additionally, when local communities’ attitudes toward perceived vi behavioural control increase, their intention to create cultural tourism destinations in the near future increases. Moreover, the results suggest that the seven behavioural beliefs, four normative injunctive beliefs, three normative descriptive beliefs, and four control beliefs underlying communities' perceptions about cultural tourism activities could positively influence their behavioural intention to create cultural tourism destinations in the future. Policymakers should consider behavioural intervention programs, technical and financial supports to reinforce positive beliefs, resulting in sustained positive behavioural intention to create future cultural tourism destinations. Future studies should consider actual behaviour, and background factors and conduct a longitudinal study to see if there could be any change in the behaviour of local communities.